Expression of the kil gene of the ColE1 plasmid in Escherichia coli Kilr mutants causes release of periplasmic enzymes and of colicin without cell death. - Suit, J L (1988)
Expression of the kil gene of the ColE1 plasmid in certain classes of Escherichia coli mutants (Kilr) resistant to kil-caused cell death brought about release of periplasmic enzymes and of colicin. Phospholipase A was present but was not activated by kil expression in any of the mutants. This indicates that in these mutants the various effects of kil gene expression have become dissociated.